2016
DOI: 10.1080/87565641.2016.1158265
|View full text |Cite
|
Sign up to set email alerts
|

Dealing With Uncertainty: Testing Risk- and Ambiguity-Attitude Across Adolescence

Abstract: Attitudes to risk (known probabilities) and attitudes to ambiguity (unknown probabilities) are separate constructs that influence decision making, but their development across adolescence remains elusive. We administered a choice task to a wide adolescent age-range (N = 157, 10-25 years) to disentangle risk- and ambiguity-attitudes using a model-based approach. Additionally, this task was played in a social context, presenting choices from a high risk-taking peer. We observed age-related changes in ambiguity-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(173 citation statements)
references
References 56 publications
13
145
6
Order By: Relevance
“…However, ambiguity attitudes (known outcomes but unknown probabilities) showed nonlinear developmental trends, with ambiguity tolerance peaking in adolescence. This finding is in line with two previous studies that also found adolescents to be more tolerant of ambiguity than adults2022, but contradicts another recent study suggesting that children may be even more ambiguity tolerant24. More importantly, we found a similar nonlinear developmental trajectory in respondents’ uncertainty attitude.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, ambiguity attitudes (known outcomes but unknown probabilities) showed nonlinear developmental trends, with ambiguity tolerance peaking in adolescence. This finding is in line with two previous studies that also found adolescents to be more tolerant of ambiguity than adults2022, but contradicts another recent study suggesting that children may be even more ambiguity tolerant24. More importantly, we found a similar nonlinear developmental trajectory in respondents’ uncertainty attitude.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, adults’ risk and ambiguity attitudes do not appear to be correlated21. At the same time, two recent studies suggest that adolescents are more ambiguity seeking than adults2022 (but see ref. 23), and another study suggests that young children may be ambiguity neutral24.…”
mentioning
confidence: 94%
“…To date, minimal research has considered how adolescents respond to differences in the predictive validity of a stimulus. However, recent evidence has indicated that adolescents more readily engage in behaviors for which the outcome is uncertain relative to adults [61, 62]. Furthermore, mounting evidence in adults indicates that the reinforcement history of a cue influences both initial and long-term learning about the cue’s meaning, as well as the responses that occur in the presence of the cue [63–69].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, adolescents exhibit a greater willingness to engage in behaviors for which the outcome is uncertain relative to adults [94, 95]. Encountering an ambiguous stimulus indicates the need to consider the information at hand and potentially acquire more information before making a decision [94, 96].…”
Section: Implications For Understanding Adolescent Behaviormentioning
confidence: 99%
“…It has previously been shown in humans that children, like adolescents, are more tolerant of ambiguity than adults [97], and furthermore, that ambiguity tolerance decreases linearly across development into adulthood [95]. Thus, additional factors must be contributing to the ontogeny of negative occasion setting to account for the non-linearity of behavioral performance.…”
Section: Implications For Understanding Adolescent Behaviormentioning
confidence: 99%